PART OF SPEECH MASTERY OF THE EIGHTH GRADE STUDENTS TAUGHT BY USING WHISPER CYCLES GAME - Muh Shofiyuddin (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris)
There are many students feel difficult in mastering English, especially in written one. The students can write well when they master the basic of English writing. It is the part of speech. An observation result of the students in the eight grade in some schools in kudus shows that many of them have the same problem. After finding the case, the writer applies this research in a school in to help the students master the part of speech. The objective of this research is to find out whether there is any significant differences or not, between the eighth grade students?? mastery of part of speech taught by using Whisper Cycles Game and taught by using Three Phases Technique. This is an experimental research design using control group. the variables are whisper cycles game as independent variable and the mastery of part of speech of the eighth grade students as dependent variable. It takes two classes as the sample, VIII A as the control group and VIII B as the experimental group. The writer uses test to get the accurate data. After conducting this research, the writer found the highest score is 92 and the lowest one is 68 from the data of the experimental group. The mean of the whole scores is 75.24 and the standard deviation is 6.60. Meanwhile, for the control group, the writer found the highest score is 78 and the lowest one is 60. The mean of the whole scores is 68.93 and the standard deviation is 5.16. It can be concluded that there is a significant difference between the mastery of part of speech of the eighth grade students taught by using whisper cycles game and by using three phases technique. Teachers should use the technique to teach the students and be more active in teaching while the students should practice more and may use the games out of formal condition. Keywords: part of speech, wishper cycles game, junior high school students